EFFECTIVENESS OF YOUNG ARECA NUT ON THE GROWTH OF VIBRIO CHOLERAE AND ESCHERICHIA COLI BACTERIA - Deborah Angelin Purba; Juli Elisabeth Mayen Meliala; Juli elisabeth mayen; Hanna Christsela Purba; Erika Yolanda Ginting; Ricky Kinarta Sembiring; Edy Fachrial (Universitas Negeri Gorontalo, 2022)
Diarrhea is caused by impaired intestinal absorption of food and beverages (such as carbohydrates, fats, and proteins) contaminated with bacteria such as Vibrio cholerae and Escherichia coli. The purpose of this study was to determine the effect of giving young areca nut seeds and what percentage of the concentration had a very good effect on overcoming the growth of Vibrio cholerae and Escherichia coli bacteria. To determine the effect of giving young areca nut and what percentage of concentration has the best effect on overcoming bacterial growth of Vibrio cholerae and Escherichia coli bacteria. The sample used is 5kg. Type of research is True Experimental and the research design is Post-Test Only Control Design the data in this study will be analyzed using SPSS Version 27 software. The concentration of the extract was made into 4 concentrations, namely 20%, 40%, 60%, 80%, and positive control (Ciprofloxacin). Furthermore, the inhibition test was carried out on the two bacteria, namely Vibrio cholerae and Escherichia coli were conducted using NA (Nutrient Agar) media. Research shows that extracts from young areca nut (Arecha catechu L.) seeds can inhibit the growth of both bacteria at high concentrations 20%, 40%, 60%, 80%, and positive control (Ciprofloxacin) with an average diameter of the inhibitory zone test for Vibrio cholera were 13.3 mm, 11.5 mm, 13.4 mm, 13.8 mm and 21.3 mm. And for the power test, the inhibition zones of Escherichia coli were 12.8 mm, 11.5 mm, 11.9 mm, 11.9 mm, 19,4 mm. This study showed that the extract (Arecha Catechu L.) affected the growth effectiveness of Vibrio cholerae and Escherichia coli bacteria from 4 concentrations, namely 20%, 40%, 60%, and 80%. The effect of young areca nut (Arecha Catechu L.) on bacteria was highest at a concentration of 60%.